MINAT AKSEPTOR KB DALAM MELAKUKAN KUNJUNGAN ULANG DI PUSKESMAS TANJUNG PAGAR BANJARMASIN - Yunita, Laurensia; Ika Mardiatul Ulfa; Ahmad Hidayat (LPPM Universitas Sari Mulia, 2022)
Background: Interest is a feeling of liking or attraction toward something or an activity without coercion. Interest essentially involves acceptance of a relationship between oneself and something outside oneself; the stronger this relationship, the greater the interest. Interest is considered a positive trait, as it begins with a sense of attraction to a particular stimulus. Moreover, interest is regarded as more active than passive, as it can motivate individuals to move toward what they are interested in. Objective: To determine the factors influencing interest in the use of implant contraceptive methods in the Tanjung Pagar Health Center area. Method: This research used a non-experimental, descriptive design with a cross-sectional approach. The sample consisted of 60 contraceptive acceptors at Tanjung Pagar Public Health Center. The sampling technique used was accidental sampling. Results: The study found that out of 60 contraceptive acceptors at Tanjung Pagar Health Center, the majority—38 individuals (63.3%)—showed interest in implant contraceptive methods, while 15 individuals (25%) were not interested. Conclusion: Interest can influence individuals to take action. It begins with the knowledge they possess, which then drives their interest to pursue something they desire. Therefore, interest can influence individuals to attend family planning visits. Keywords: Acceptors, Follow-up Visits, Interest